Profiling 4C Skills Through PISA-Based Mathematics Tasks: A Contextual Analysis of Junior High School Students - Simanjuntak, Sinta Dameria; Saragih, Sahat; Sitepu, Israil; Noverica, Sondang (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
The 4C skills—Critical Thinking, Creativity, Communication, and Collaboration—are essential for preparing students to navigate 21st-century challenges. However, results from PISA 2022 and Indonesia's Education Report 2024 reveal that foundational competencies remain low, particularly in rural contexts. This study aims to explore the manifestation of 4C skills among ninth-grade students at SMP Budhi Dharma Balige, North Sumatra, through performance on PISA-based mathematics questions. Employing a qualitative descriptive design, data were collected from 31 students using two PISA tasks and an unstructured teacher interview. Responses were assessed using a rubric-informed framework, and analysis followed the Miles and Huberman model. Results show that while students demonstrate strong communication and procedural reasoning (96.77% correct in Q1 Part 2), performance in critical thinking and argumentation remains limited (only 35% success in Q2 Part 3). The main barrier is the lack of integrated instructional strategies that promote higher-order and collaborative learning. The study concludes that while 4C skills are beginning to develop, their progression is fragmented and requires targeted pedagogical reforms. Recommendations include the use of project-based learning, culturally responsive instruction, and formative assessments to ensure equitable 4C development in under-resourced schools.